A refinement of an inequality due to Ankeny and Rivlin - TRIPATHI, Dinesh (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
Let p(z)= _ u =0^n a_ u z^ u be a polynomial of degree n, M(p,R):= _|z|=R 0 |p(z)|, and M(p,1):=M(p). Then by well-known result due to Ankeny and Rivlin Ankeny, we have M(p.R)≤(Rn+12)M(p), R≥1. In this paper, we sharpen and generalizes the above inequality by using a result due to Govil Govil1989. Mathematics Subject Classification (2010): 15A18, 30C10, 30C15, 30A10.